The development of the continental rule through law - Nadia E. Nedzel (Duke University, Center for the History of Political Economy (CHOPE), 2019)
This will be the third chapter in a forthcoming book on the Rule of Law, Economic Development, and Corporate Governance. The first chapter will introduce the books themes and theses, the second (already on SSRN) gives the history of the development of the English concept of the Rule of Law, and this chapter discusses the development of the similar civil law concept, the Rule through law, otherwise known as Rechtsstaat.
Keywords: 330